MaPPeRTrac: A Massively Parallel, Portable, and Reproducible Tractography Pipeline - Lanya T. Cai; Joseph Moon; Paul B. Camacho; Aaron T. Anderson; Won Jong Chwa; Bradley P. Sutton; Amy J. Markowitz; Eva M. Palacios; Alexis Rodriguez; Geoffrey T. Manley; Shivsundaram Shankar; Peer-Timo Bremer; et al. (Neuroinformatics, 2024)

Dusky dolphin movement patterns: short‐term effects of tourism - D Lundquist; NJ Gemmell; B Würsig; T Markowitz (New Zealand Journal of Marine and Freshwater Research, 2013)
Cetacean‐oriented tourism has experienced rapid growth in the last two decades, accompanied by increasing concerns about the effects of tourism on target species. Here, we used shore‐based observations of dusky dolphin ( Lagenorhynchus obscurus ) groups near Kaikoura, New Zealand, and generalised additive models to quantify changes in group speed, reorientation and linearity relative to natural and anthropogenic factors. Summer months were characterised by slower speeds and more changes in direction than winter months. Group speeds were higher at the beginning and end of the day, with slower speeds at midday. Speeds were slower when vessels were present, and dolphin groups changed direction more often when aircraft circled overhead. Effects were positively correlated with number of vessels present within 300 m. Short‐term changes have potential to lead to long‐term impacts, and further acoustic and energetic studies are proposed to elucidate whether these effects are likely to reduce individual fitness.

D igital P hotography I mproves E fficiency O f I ndividual D olphin I dentification : A R eply T o M izroch - T. M. Markowitz; A. D. Harlin; B. Würsig (Marine Mammal Science, 2003)

Abstracts of presentations at the 22nd Congress of the Israeli Phytopathological Society February 12–13,2001 ARO, The Volcani Center, Bet Dagan, Israel - D. Shtienberg; M. Reuveni; N. Shegalov; D. Shegalov; D. Eshel; Ruth Ben-Arie; D. Prusky; Nadia Korolev; J. Katan; Talma Katan; A. Sharon; L. Oren; et al. (Phytoparasitica, 2001)